Motivasi Kerja, Kepuasan Kerja, Dan Disiplin Kerja Terhadap Kinerja Karyawan Mc Donald's - Vira Yuniar Indrayana; Larasati Ayu Sekarsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze the significance of the influence of work motivation, job satisfaction, work discipline on employee performance at McDonalds Surabaya. The method used in this research is descriptive with a quantitative approach. From the results of the research above, it can be concluded that work motivation has a significant positive effect on employee performance at McDonalds Surabaya. While good performance can improve organizational performance in order to achieve company goals. Job Satisfaction has a significant effect on Employee Performance at McDonalds Surabaya. This shows that the higher the employee's job satisfaction, the higher the employee's performance. Work Discipline has no significant effect on Employee Performance at McDonalds Surabaya. Without work discipline from employees, it will be difficult for companies to get optimal results, because employee performance is not good. From discipline, good morale will emerge, because it is this discipline that shapes the character of employees. Keywords: Work Motivation, Job Satisfaction, Work Discipline